Ambipolar MoTe2 Transistors and Their Applications in Logic Circuits. (1st April 2014) - Lin, Yen‐Fu; Xu, Yong; Wang, Sheng‐Tsung; Li, Song‐Lin; Yamamoto, Mahito; Aparecido‐Ferreira, Alex; Li, Wenwu; Sun, Huabin; Nakaharai, Shu; Jian, Wen‐Bin; Ueno, Keiji; Tsukagoshi, Kazuhito
<x xml:space="preserve">Abstract</x> We report ambipolar charge transport in α‐molybdenum ditelluride (MoTe2) flakes, whereby the temperature dependence of the electrical characteristics was systematically analyzed. The ambipolarity of the charge transport originated from the formation of Schottky barriers at the metal/MoTe2 contacts. The Schottky barrier heights as well as the current on/off ratio could be modified by modulating the electrostatic fields of the back‐gate voltage (Vbg) and drain‐source voltage (Vds). Using these ambipolar MoTe2 transistors we fabricated complementary inverters and amplifiers, demonstrating their feasibility for future digital and analog circuit applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>